THE ROLE OF MUSLIM WOMEN IN THE GLOBAL ECONOMY - Nurhafna Balqis; Anggi Syahfitri Siahaan; Khairani Hayat Situmorang (CV. Barokah Publsiher, 2026)
This study aims to analyze the role of Muslim women in the global economy by examining their participation across various economic sectors, identifying key challenges, and exploring opportunities within the context of globalization and inclusive development. The research employs a qualitative approach using a systematic literature review (SLR) method, drawing on secondary data from peer-reviewed journals, academic books, and international institutional reports. The data are analyzed through thematic synthesis to identify patterns related to economic participation, structural barriers, and enabling factors. The findings reveal that Muslim women’s participation in the global economy has increased significantly, particularly in entrepreneurship, education, healthcare, and digital industries. This growth is strongly supported by improvements in education, financial inclusion, and access to technology. However, the study also finds that socio-cultural norms, gender inequality, and institutional barriers continue to limit the full economic potential of Muslim women, especially in developing regions. Furthermore, the interaction between enabling and constraining factors plays a decisive role in shaping economic outcomes. The study highlights that Islamic economic principles, when interpreted inclusively, can support women’s economic empowerment by promoting justice, equity, and ethical participation. The novelty of this research lies in its integrative approach, combining perspectives from gender studies, Islamic economics, and globalization to provide a more comprehensive understanding of Muslim women’s economic roles. The study concludes that empowering Muslim women contributes not only to individual welfare but also to broader economic development, including poverty reduction and sustainable growth.